The Theory of Economic Transaction costs: apply in Institutions of Higher Education in Nicaragua (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2016)
The objective of the research was to answer the following question to what extent the theory of transaction costs, incomplete information does and markets can be applied in the Nicaraguan University system. To carry over the research it was applied the inductive- deductive method of analysis. The database utilized was information from University library paid subscription and free available information coming from scholar search engines. The results suggested that there is little literature that considers direct transaction costs in the academic dimension. This finding reflects the existence of information gaps and insufficient alignment of University the Nicaraguan Council of Universities CNU. Giving that result it is important to consider factors and indicators that can show economic transaction with the customers and users of tangible and intangible products that the university system generates. However, University stillfaces a demand for innovation in its broadest sense.
Keywords: Universities; Economic Transaction Costs. . Interactive Learning. Innovation; cognitive Products; Institutions